The efficacy of dermoscopy in defining the surgical margins of cutaneous squamous cell carcinoma: a retrospective study - Liu, Zhenru; Huang, Shudai; Li, Fang; Wang, Xiaoqing; Liu, Mengxi; Wong, Hoi Shiwn; Jiang, Jiayi; Zhou, Yuan; Wang, Daguang (Frontiers in Oncology, 2023)
Objective: To investigate the diagnostic value of dermoscopy in defining the tumor margin of cutaneous squamous cell carcinoma (cSCC) for the appropriate surgical margin. Methods: A total of 90 cSCC patients were enrolled in the study. All patients were recruited into two groups: those who preserved intact macroscopic features of neoplasms without or after incisional biopsy and those with uncertain residual tumors after excisional biopsy. A dermoscopy-defined surgical margin of 8mm outward was used according to the tumor boundaries observed with the naked eye and dermoscopy. All excised tumor specimens were divided into serial sections according to the four "3, 6, 9, 12" directions at every 4-mm interval from the dermoscopy-detected tumor margin. Pathological examination was performed at 0 mm, 4 mm, and 8 mm margins to confirm tumor remnants. Results: Retrospective analysis of dermatoscopic results showed inconsistent clinical and dermatoscopic borders in 43 of 90 cases (47.8%). The preoperative dermoscopic observation allowed for a more microscopic correction of margins, with 38.9% having wider dermoscopic borders and 8.9% having narrower ones. The ability of dermoscopy to detect tumor borders showed no statistical difference between the two groups (p > 0.05). In the unbiopsy or incisional biopsy group, 66.6% of the tumors were resected with a 4-mm margin and 98.3% with an 8-mm margin, with significant differences (p = 0.047). For patients with inconspicuous clinical evidence of residual tumor after excisional biopsy, the tumor clearance rate was 53.3% at 0 mm, 93.3% at 4 mm, and 100.0% at 8 mm. Statistically significant differences were noted between 0 mm and 4 mm (p = 0.017), as well as between 0 mm and 8 mm (p = 0.043) but did not differ between 4 mm and 8 mm (p>0.05). Conclusions: Dermoscopy defined the tumor margin of cSCC better than visual inspection alone. Direct dermoscopic-guided surgery with at least 8-mm expansion was recommended for high-risk cSCC . Dermoscopy also assisted in identifying surgical margins at the healing biopsy site, making 8 mm still the recommended expansion range.